The Effect of Health Education Using Brainstorming and Audiovisual Methods on the Knowledge of Families of Tuberculosis Patients - Achmad Wahdi; Moh. Alimansur; Erik Irham Lutfi; Dewi Retno Puspitosari (Jurnal Ilmiah STIKES Yarsi Mataram, 2026)
Tuberculosis is an infectious disease caused by the Mycobacterium tuberculosis bacteria. Poor family and community knowledge about pulmonary TB has a greater risk of increasing cases of pulmonary TB, while families and communities with good knowledge about pulmonary TB can reduce the incidence of pulmonary TB cases. This study aims to determine the Effect of Health Education Using Brainstorming and Audiovisual Methods on the Knowledge of Families of Tuberculosis Patients. This study is a pre-experimental study with a one-group pre-post-test design. The population is 35 families of tuberculosis patients at the Ngasem Community Health Center, Kediri Regency. The sample size is 35 families of patients selected using a non-probability sampling technique. The research instrument uses a knowledge level questionnaire. Data analysis uses the Wilcoxon test. The results of the Wilcoxon Signed Ranks Test in SPSS, with a significance value of p value = 0.000 <0.05, meaning H1 is accepted, which means there is an Effect of Health Education Using Brainstorming and Audiovisual Methods on the Knowledge of Families of Tuberculosis Patients. Health centers can use Health Education Using Brainstorming and Audiovisual Methods to increase the knowledge of families of tuberculosis patients.